PENERAPAN TERAPI RITME (RHYTYM THERAPY) UNTUK PENDERITA AUTIS (AUTISM) PADA PEMBELAJARAN PIANO-KEYBOARD DI GILANG RAMADHAN STUDIO BAND (GRSB) TEGAL - nurani, irfan (Jurnal Seni Musik, 2015)
Therapy rhythm is a therapy for stroke patients by means of moving the member body adjusts to the rhythm / rhythm of the music, was originally developed by Ronnie Gardiner a jazz drummer from the USA and then in early 2008 music school Gilang Ramadhan Studio Band (GRSB) to expand that to be applied to the tool music like drum and keyboard so that a new breakthrough in the world of learning drums and keyboard. This study used a qualitative approach. Data collection techniques including observation, interviews, and documentation. Mechanical examination of the validity of the data using triangulation confidence level, which includes triangulation, triangulation method, and triangulation of data. Data analysis technique used is the technique of interactive analysis include: data reduction, data presentation, and conclusion. The results showed that the application of therapeutic rhythm (Rhythm Therapy) for children with autism (autism) on learning piano-keyboard in Gilang Ramadhan Studio Band (GRSB) in Tegal emphasis on the provision of material rhythm more intensive with the aim of creating a cure by using 9 learning program , Factors supporting the implementation rhythm therapy is divided into internal and external factors. No limiting factor on the teacher who had difficulty in presenting the material.